Sadaqah in the Light of Prophetic Hadiths : (A Study Of The Asbāb Al-Wurūd Of Hadith Muslim No. 1006) - Sohibul Haq (مجلة النور الدولية للقرآن والحديث, 2023)
This paper discusses the asbāb al-wurūd of the hadith about charity not being limited to wealth alone. This hadith needs to be known and studied because some human beings are still stereotyped that charity can only be done with property. Understanding that ignores the asbāb al-wurūd. Usually, many are trapped in textual meanings that encourage misunderstanding. This paper analyzes the hadith about almsgiving using a qualitative method with the takhrij, sharah, and asbāb al-wurūd hadith approach. This research also uses the Library Research method to explore more in-depth information. This research found several essential points, including that charity for materially capable people can be replaced by reciting ṭayyibah sentences (al-ḥamd lillāh, Allāh Akbar, Subhān Allah, and the sentence Lā ilāha Illa Allāh) or by pointing to the good and forbidding the bad. This aligns with the Hadith narrated by Imam Muslim with Index No. 1006. Besides that, it turns out that sadaqah has many benefits, one of which can reduce liver disease that clots inside.